The morphological effects of hydrothermal carbon on mechanical, tribological and corrosion properties of AlSi12 composite. (30th August 2021) - Simsir, Hamza
Abstract: Although aluminum and its composites have been used in many applications, their mechanical properties should be improved for use in wider applications. Hence, specially nanosized and sub-micron sized carbonaceous additives were used. As far as is known, hydrothermal carbons (HTCs) have not yet been used in aluminum-silicon matrix composites. In this study, two different morphologies of HTCs were synthesized from cellulose and chitosan. With the use of chitosan, the particle morphology of HTCs was changed from hard spheres to smaller aggregated spheres. Both HTCs had a positive effect on mechanical (hardness >%18, and ultimate compression strength >%9) and tribological properties (wear rate >% 14) and they caused only limited decrement of corrosion resistance (corrosion rate <%13). The aggregated spheres possessed HTCs presented better mechanical, tribological and corrosive properties than those the hard spheres possessed.